Respon Pertumbuhan Nodus Artemisia vulgaris L pada Medium Murashige-Skoog dengan Penambahan Beberapa Zat Pengatur Tumbuh Secara In Vitro - Novia Rika Deli; Zozy Aneloi Noli; Suwirmen Suwirmen (Jurnal Biologi Universitas Andalas, 2015)
Artemesia vulgaris L produce artemisinin which is effective against resistant strains of Plasmodium falciparum, the malarial parasite. The study about growth responses of Artemesia vulgaris L in Murashige-Skoog (MS) medium supplemented with several growth regulators had been done from September to November 2014 at the Laboratory of Plant Phisiology and Tissue Culture, Department of Biology, Faculty of Mathematic and Natural Science, Andalas University. The aims of the study was to know the responses of node explants of Artemesia vulgaris L supplemented with several plant growth regulators for the effective technique of propagation. The study used Completely Randomized Design with four treatments and six replications. Node from in vitro growth were treated with three different kind of growth regulator (0.3 ppm BAP, 0.5 ppm NAA, 0.3 ppm GA3) in MS medium. The result showed that 0.5 ppm NAA was the best growth regulators formed callus, bud, and root of Artemesia vulgaris L.Keywords: Artemesia vulgaris L, plant growths regulator, in vitro